Factor influencing the purchase of takaful among working youth in Kota Bharu Kelantan. - Zulkifli Mohd Zan (2020)
This research is to study the factor influencing the purchase of takaful among youth in Kota Bharu. The purpose of the study among working youth because they have their own careers and income. This can influence them to buy or contribute takaful. Youth age is between 15 years to 40 years until 2021 and the age limit of youth will be lowered to 15 years to 30 years. According to Youth and Sports Minister Syed Saddiq Syed Abdul Rahman (2019), he said the youth age limit transition plan would only officially begin at the end of December 2021.This study target place area in Kota Bharu because Kota Bharu is a State Center for Kelantan, and population distribution that many because there are many government departments, shopping mall, as well as a centre for trade.